2019
DOI: 10.2478/mgr-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

The countryside in the city? Rural-urban dynamics in allotment gardens in Brno, Czech Republic

Abstract: The position of urban allotments in the rural-urban spectrum is evaluated in this paper, which contributes to literatures on urban gardening, as well as contemporary rural-urban dynamics. Historically, European allotments can be seen as a product of urbanisation. At the same time, they embody a number of “non-urban” characteristics that create the impression of “the countryside in the city”. This research project investigates how the urban and the rural are materialised, represented and practised in five allot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…This is a process similar to that in other European countries [1][2][3]9,[13][14][15][16][17][18]. So far, allotment gardens in the Tri-City have been moved from their previous locations to new, less prestigious ones, as was the case in other countries [2,17,18,24,25]. Despite this, the analyzed allotments were left, the aesthetics of which are taken care of by the managers, so as to limit the number of conflicts generated by them.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This is a process similar to that in other European countries [1][2][3]9,[13][14][15][16][17][18]. So far, allotment gardens in the Tri-City have been moved from their previous locations to new, less prestigious ones, as was the case in other countries [2,17,18,24,25]. Despite this, the analyzed allotments were left, the aesthetics of which are taken care of by the managers, so as to limit the number of conflicts generated by them.…”
Section: Discussionmentioning
confidence: 84%
“…Similar issues were discussed in the articles concerning Prague [24] and Brno [25]. In the former, the authors remind the reader that the allotment gardens were created based on the political and ecological process of urbanization of nature, dictated by the communist authorities in 1948-1989, and later by neo-liberal governments.…”
Section: Review Of Research On Allotment Gardensmentioning
confidence: 87%
“…Regarding the special benefited groups, only 16 articles [27,28,31,33,34,36,[38][39][40][41][42][43][44][45][46][47] have recorded such specific benefited groups from particular urban agriculture practices, which include older adults, migrants, low-income people, disabled people, people with mental disorders, school children, cancer patients, and women (Table S1). However, the Health and emotional benefits were recorded more than twice as much in developed countries [17,26,27,36,[38][39][40]46,47,49,50,52,53,[56][57][58][59][60][61] compared to developing countries [29,59,[62][63][64][65][66] (Table 2). The top three health and emotional sub-categories recorded in developed countries are food nutrition and quality, connection with nature, physical activity, and mental relaxation.…”
Section: Special Benefited Groups Land Ownership and Government Supportmentioning
confidence: 99%
“…This type of organized urban gardening has been declining since 1989, both in terms of land area and the number of allotment members Spilková and Vágner, 2016). During my field research conducted in allotments in Brno, several gardeners expressed the opinion that social cohesion was stronger during socialist times, whereas nowadays gardens are used in a more individualized manner, and common activities are less frequent (Sovová and Krylová, 2019). A representative survey from 2015 (unpublished) revealed that some Czechs currently feel less involved in informal food economies compared to 10 years ago (questions focused on topics such as FSP, self-help repairs and housework and receiving and giving help).…”
Section: Rethinking Food Self-provisioningmentioning
confidence: 99%
“…16 I am aware that the association of food production with the countryside is based on the modernist conceptualization of the city and the countryside, which does not necessarily capture current realities in many places of the world. In other words, one should be careful in assuming that rural dwellers are by default more connected with their food system (seeSovová and Krylová, 2019, for a discussion of this issue).…”
mentioning
confidence: 99%